2015
DOI: 10.4306/pi.2015.12.1.146
|View full text |Cite
|
Sign up to set email alerts
|

A Long Term Effects of a New Onset Psychosis after DBS Treated with Quetiapine in a Patient with Parkinson's Disease

Abstract: Deep Brain Stimulation represents a therapeutic option for PD patients. In this paper, we present and discuss a case of acute delirium and psychosis manifesting after DBS in a 58-years-old man affected by Parkinson's Disease. We highlight the importance of an exhaustive psychiatric evaluation in candidates for DBS and we underline the severity and non-reversibility of some adverse events associated with the implantation, suggesting the use of Quetiapine in the management of these effects. Acute psychosis may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Currently for geriatric population, PD symptoms are being managed with either surgical intervention (deep brain stimulation) or medications (L‐DOPA or dopamine D2 receptor agonists), and despite these methods displayed positive outcome in controlling the symptoms, their effects were rather short‐lived, thus requiring higher dosage of same treatment to mimic similar recovery latency . Lately, cell replacement therapy (CRT) has been regarded as the next possible solution to such medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently for geriatric population, PD symptoms are being managed with either surgical intervention (deep brain stimulation) or medications (L‐DOPA or dopamine D2 receptor agonists), and despite these methods displayed positive outcome in controlling the symptoms, their effects were rather short‐lived, thus requiring higher dosage of same treatment to mimic similar recovery latency . Lately, cell replacement therapy (CRT) has been regarded as the next possible solution to such medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of 808 publications covering the years 1996–2005, the most common psychiatric side effect associated with DBS was delirium, making up 4 to 8% of all psychiatric complications (Appleby et al, 2007 ). The psychiatric side effects of DBS are usually transient and treatable (Voon et al, 2006 ), but there have been case reports of very severe side effects with long-term consequences (Zonana et al, 2011 ; Piccoli et al, 2015 ). Other researchers reported an improvement of psychiatric symptoms after DBS (Funkiewiez et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study described delirium as any degree of hallucination, confusion, or spatial disorientation [ 17 ]. In addition, a case report described a patient who, under delirium after DBS surgery, showed delusions, hallucinations, confusion, and very aggressive behavior within 48 hours following the implantation and activation of the electrode [ 18 ].…”
Section: Definition and Clinical Criteriamentioning
confidence: 99%
“…Currently, some researchers believe that quetiapine is the safest choice for delirium treatment in PD patients [ 59 ]. In patients who received DBS, quetiapine has been shown to be able to control delirium following DBS surgery [ 18 , 22 ]. In addition, a case report showed that Zolpidem improved psychiatric symptoms after DBS.…”
Section: Prevention and Treatment Of Delirium After Dbsmentioning
confidence: 99%